Synthesis and Biological Evaluation of Some New Benzimidazole Derivatives as Antimicrobials - Modi, Amit (International Journal of Pharmaceutical & Biological Archive, 2015)
Synthesis and Biological Evaluation of Some New Benzimidazole Derivatives as Antimicrobials